(untitled) (University of Khartoum Engineering Journal, 2022)
The Restartability of the Sudanese Nile Blend crude oil inside Test Loop pipeline was performed tounderstand the parameters determining the yield stress and describe the process of yielding up to final lineclearing. Test Loop is designed to find the relationship between the required restart time and the pressure requiredand also to find the blend yield stress. The yield stress of the Nile Blend was found to be affected significantly bythe shutdown time, static cooling rate after shutdown, and the final temperature after shutdown.